EFEKTIFITAS MEDIA VIDEO TERHADAP PENGETAHUAN SADARI - Maryuni Maryuni; Irwanti Gustina; Ria Irawan (JOMIS (Journal of Midwifery Science), 2022)
Data from the Global Burden of Cancer (GLOBOCAN) released by the World Health Organization (WHO) states that the number of cases and deaths from cancer until 2018 was 18.1 million cases and 9.6 million deaths in 2018. This study aims to determine the effectiveness of health education for adolescents aged 15-20 years with video media on Knowledge of Breast Self-Examination The method used in this study was the Quasi-Experimental method, the quasi-experimental design used was "One-Group Pretest-Posttest Design". ", which consists of one group of subjects, the population in the study is adolescents aged 15-20 years at SMAN 14 Jakarta for the 2020/2021 period. The research sample was selected using the Random Cluster sample technique. In this study bivariate analysis was carried out to determine the effectiveness of video media in knowledge about BSE, was carried out using the Wilcoxon Sign Test. If p < 0.05 then there is a significant effect meaning at the level of effectiveness of video media during the pretest and posttest. The results showed that the health education intervention about BSE given through video media to SMAN 14 Jakarta students could increase the knowledge of students by 5, from 3 (before the intervention) to 8 (after the intervention). intervention)